Study on the castability and mechanical properties of thin-walled nickel-base superalloy. Issue 3 (11th February 2017) - Kang, M. D.; Wang, J.; Gao, H. Y.; Han, Y. F.; Shu, D.; Lai, X. M.; Sun, B. D.
Abstract : The castability and mechanical properties of thin-walled nickel-base superalloy castings fabricated by gravity casting and centrifugal casting were investigated. It is shown that, despite its microporosity has slight change, the casting fabricated by centrifugal casting presents fewer misruns and less Laves phase than that of gravity casting. The ultimate tensile strength, yield strength and stress rupture lives of centrifugal casting are improved by about 2.2, 7.4 and 41.1%, respectively. However, the elongation (EL) and reduction in area are sharply decreased by about 10.9 and 25.0%, respectively. Paradoxically, the stress ELs of both castings are similar. The seemingly contradictory results in mechanical properties stem from the opposite effects of centrifugal force on hardening elements macrosegregation and melt turbulence.